Penerapan Algoritma TOPSIS Dalam Penentuan Prioritas Calon Agen Perubahan Pada Kantor Pengadilan - Zainal Fahriandy; Bahar Bahar (STMIK Banjarbaru, 2022)
Considering the importance level of each parameter becomes very ideal in determine priorities. However, this concept has not been applied in the process of selecting candidates for change agents in all District Court offices in Indonesia, so the process becomes less accurate. This paper examines the application of the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) algorithm in determining the priorities of prospective change agent employees at the District Court office, with a case study at the Martapura District Court Office. Parameters of Innovation, Behavior, Discipline, Responsibility, and Communication become a reference in determining the priority order of candidates. Each parameter is given a weight according to the level of importance that has been formulated by policy makers, then the average value obtained from the results of the assessment of each parameter is processed using the TOPSIS algorithm. The system accuracy test is carried out by comparing the process results without parameter weighting and the process results with a parameter weighting system. Based on the 16 cases tested, the TOPSIS accuracy rate reached 100%, so it deserves to be considered a decision support tool.Keywords: Decision support system; Parameter importance level; Accuracy testing Abstrak. Memperhitungan tingkat kepentingan setiap parameter menjadi sangat ideal dalam penetapan prioritas. Namun konsep ini belum diterapkan dalam proses pemilihan calon pegawai agen perubahan di seluruh kantor Pengadilan Negeri tingkat Kabupaten/kota di Indonesia, sehingga proses menjadi kurang akurat. Makalah ini menguji penerapan algoritma Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) dalam penetapan prioritas calon pegawai agen perubahan pada kantor Pengadilan Negeri, dengan studi kasus pada Kantor Pengadilan Negeri Martapura. Parameter Inovasi, Perilaku, Disiplin, Tanggung Jawab, dan Komunikasi menjadi acuan dalam menetapkan urutan prioritas calon. Setiap parameter diberi bobot sesuai dengan tingkat kepentingan yang telah dirumuskan oleh pengambil kebijakan, selanjutnya rerata angka yang diperoleh dari hasil penilaian setiap parameter diproses menggunakan algoritma TOPSIS. Uji akurasi sistem dilakukan dengan membandingkan hasil proses tanpa pembobotan parameter dan hasil proses dengan sistem pembobotan parameter. Berdasarkan 16 kasus yang diuji, tingkat akurasi TOPSIS mencapai 100%, sehingga layak dipertimbangkan menjadi alat pendukung pengambilan keputusan.Kata Kunci: Sistem pendukung keputusan; Tingkat kepentingan parameter; Uji Akurasi